BESE-SONO IN THE ATONI PAH METO COMMUNITY: THEOLOGICAL PERSPECTIVE OF ST. AUGUSTINE’S LOVE IN THE PRACTICE OF CULTURAL SOLIDARITY - Ukat, Kristophorus; Firmanto, Antonius Deny; Sihombing, Adison Adrianus; Banusu, Yeremias (Balai Penelitian dan Pengembangan Agama Jakarta, 2025)
This article analyzes the practice of bese-sono in the Atoni Pah Meto society as a manifestation of love for God, using the theological perspective of Saint Augustine. Employing a qualitative approach, this study utilizes both primary and secondary data. Primary data were obtained through in-depth interviews with key informants, including religious leaders, traditional leaders, community leaders, educational leaders, government leaders, and ordinary people (10 in total). Secondary data were gathered through a literature review of sources relevant to the topic. The findings reveal that bese-sono is a manifestation of deep love, where self-sacrifice for the common good becomes a concrete expression of love for God and others. This is demonstrated through social rituals. In this context, Augustine's teachings on love for God provide a theological foundation for understanding the practice of bese-sono as an expression of solidarity that unites members of the community. This is possible because a deep understanding of the values of love can shape a harmonious social life and strengthen relationships among individuals in the broader society. Thus, this study offers a new theological perspective on sacrifice and solidarity in local communities, enriching the field of social theology.